Superselective embolic particle guidance in vessel networks via shape-adaptive acoustic manipulation - Yucheng Luo; Qiu Yin; Keke Chen; Zhaoyu Deng; Xiaozhou Liu; Yinning Zhou; Benpeng Zhu; Wenming Zhang; Zhichao Ma (Nature Communications, 2025)
Abstract Interventional embolization has been widely used as a clinical cancer therapy, which deactivates the tumors by occluding their blood supply vessels. However, conventional methods lack active control over the embolic particles, thus having a limited selectivity of millimeter-scale vessels and the issue of missing embolization. Here, we propose an ultrasound-based method for embolic particle control in submillimeter vessels. The biocompatible ultrasound generated from an extrasomatic source can transmit through biological tissues, and exert forces on the intravital embolic particles. We show that the particles, influenced by these forces, are steerable to the target branch at vascular bifurcations. By modulating the ultrasound to adapt the vascular bifurcation distribution, the particles flowing in the micro-vessel networks are steered to the target branch and embolize it. The acoustic steering within ex vivo and in vivo models both verify the potential of this non-invasive particle control for precise and safe interventional therapy.